2014
DOI: 10.1186/2050-6511-15-48
|View full text |Cite
|
Sign up to set email alerts
|

Higher dose versus lower dose of antiviral therapy in the treatment of herpes zoster infection in the elderly: a matched retrospective population-based cohort study

Abstract: BackgroundHigher versus lower doses of antiviral drugs used to treat herpes zoster infection may lead to more adverse drug events in older adults, particularly those with chronic kidney disease.MethodsWe conducted a matched retrospective population-based cohort study of older adults (mean 77 years) in Ontario, Canada who initiated in the outpatient setting a higher (n = 23,256) or lower (n = 3,876) dose of one of three oral antivirals for the treatment of herpes zoster between 2002 and 2011. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Higher doses of Valacyclovir may be safe as in Meur YL 18 correspondence followed the use of Valacyclovir 6-8 g/day in 6 cases after renal transplantation for prevention of cytomegalovirus and found that after 3 months, there was no increase in the serum creatinine and crystalluria was not detected. Lam NN and team 19 carried out another study, which was a matched retrospective population-based cohort study of older adults (mean 77 years) in Ontario, Canada with the outpatient setting of higher (n = 23,256) or lower (n = 3,876) dose of one of three oral antivirals for the treatment of herpes zoster (acyclovir 4,000 vs 800-3,200 mg/day; Valacyclovir 3,000 vs 500-2,000 mg/day and famvir 1,500 vs 350-1,000 mg/day), and found that a higher dose of the antiviral drug, compared to a lower dose, was not associated with an increased risk of hospitalization with an urgent head CT scan, and was not associated with a higher risk of all-cause mortality. 19 However, Valacyclovir taken 8g/day, which was seen to significantly reduce the risk of cytomegalovirus (CMV), and was found to be associated with earlier mortality in Feinberg JE 20 study (1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher doses of Valacyclovir may be safe as in Meur YL 18 correspondence followed the use of Valacyclovir 6-8 g/day in 6 cases after renal transplantation for prevention of cytomegalovirus and found that after 3 months, there was no increase in the serum creatinine and crystalluria was not detected. Lam NN and team 19 carried out another study, which was a matched retrospective population-based cohort study of older adults (mean 77 years) in Ontario, Canada with the outpatient setting of higher (n = 23,256) or lower (n = 3,876) dose of one of three oral antivirals for the treatment of herpes zoster (acyclovir 4,000 vs 800-3,200 mg/day; Valacyclovir 3,000 vs 500-2,000 mg/day and famvir 1,500 vs 350-1,000 mg/day), and found that a higher dose of the antiviral drug, compared to a lower dose, was not associated with an increased risk of hospitalization with an urgent head CT scan, and was not associated with a higher risk of all-cause mortality. 19 However, Valacyclovir taken 8g/day, which was seen to significantly reduce the risk of cytomegalovirus (CMV), and was found to be associated with earlier mortality in Feinberg JE 20 study (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lam NN and team 19 carried out another study, which was a matched retrospective population-based cohort study of older adults (mean 77 years) in Ontario, Canada with the outpatient setting of higher (n = 23,256) or lower (n = 3,876) dose of one of three oral antivirals for the treatment of herpes zoster (acyclovir 4,000 vs 800-3,200 mg/day; Valacyclovir 3,000 vs 500-2,000 mg/day and famvir 1,500 vs 350-1,000 mg/day), and found that a higher dose of the antiviral drug, compared to a lower dose, was not associated with an increased risk of hospitalization with an urgent head CT scan, and was not associated with a higher risk of all-cause mortality. 19 However, Valacyclovir taken 8g/day, which was seen to significantly reduce the risk of cytomegalovirus (CMV), and was found to be associated with earlier mortality in Feinberg JE 20 study (1998). Valacyclovir-related AKI occurred more in the summer as noticed by Inaba I 21 (2019) from the Japanese Adverse Drug Event Report (JADER) database and was assumed to be from dehydration.…”
Section: Discussionmentioning
confidence: 99%